2018
DOI: 10.3389/fmicb.2018.02392
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion Properties of Food-Associated Lactobacillus plantarum Strains on Human Intestinal Epithelial Cells and Modulation of IL-8 Release

Abstract: Food-associated microbes can reach the gut as viable cells and interact with the human host providing potential health benefits. In this study, we evaluated the impact on cell viability and the adhesion ability of 22 Lactobacillus plantarum strains, mainly isolated from fermented foods, on a Normal-derived Colon Mucosa cell line. Furthermore, due to the presence of mucus layer on the gut epithelium, we also investigated whether the mucin could affect the microbial adhesion property. Our results demonstrated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 59 publications
4
66
0
Order By: Relevance
“…Our data points towards the ability of all of the strains applied to this study, both food-borne and human isolates to survive one of the main gastro-intestinal stresses, and combined with our previous studies in an in vitro GI model 46,47 we suggest that all of the strains should be viable on reaching the duodenum and in GI transit. Microbial bile tolerance is a recognized criteria for probiotic strain selection, and BSH activity is a desirable property when selecting a strain for use as a dietary adjunct 10,13,58 .…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Our data points towards the ability of all of the strains applied to this study, both food-borne and human isolates to survive one of the main gastro-intestinal stresses, and combined with our previous studies in an in vitro GI model 46,47 we suggest that all of the strains should be viable on reaching the duodenum and in GI transit. Microbial bile tolerance is a recognized criteria for probiotic strain selection, and BSH activity is a desirable property when selecting a strain for use as a dietary adjunct 10,13,58 .…”
Section: Discussionsupporting
confidence: 79%
“…All the strains were previously characterized as Lb. plantarum species and tested for several properties including their potential ability to survive in GI transit 46,47 . They were routinely grown under microaerophilic conditions using de Man, Rogosa and Sharp (MRS) medium (Oxoid) at 37°.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table olives represent a wide reservoir of putative beneficial microbes. Thus, several studies have been conducted to assess the probiotic effects of strains isolated from different fermented olives cultivars and/or already used as starter cultures, belonging to the most widely spread species L. plantarum and L. pentosus, as well as to species less frequently used, such as L. paracasei, L. casei, and L. paraplantarum [43,85,[100][101][102][103][104][105][106]. Some studies revealed that some LAB strains isolated from table olives were able to adhere to porcine jejune epithelial cells IPEC-J2 and produced antimicrobial compounds able to inhibit Helicobacter pylori, Propionibacterium spp., and Clostridium perfringens [10,70,[107][108][109].…”
Section: New Trend In Olive Production: Probiotic Table Olivesmentioning
confidence: 99%
“…Recently, different studies have been focusing on the yeast microbiota associated with table olives fermentations in order to find potential probiotic candidates to be used as starter cultures [23,26,54,[100][101][102][103][104][105][106]. Saccharomyces boulardii represent the only yeast with claimed probiotic effects [120].…”
Section: New Trend In Olive Production: Probiotic Table Olivesmentioning
confidence: 99%